Efficacy and Safety of Vadadustat for Anemia in Patients With Chronic Kidney Disease: A Systematic Review and Meta-Analysis - Xiong, Limei; Zhang, Hui; Guo, Yannan; Song, Yue; Tao, Yuhong (Frontiers in Pharmacology, 2022)
Background: Vadadustat is a novel drug for treating anemia patients with chronic kidney disease (CKD), but its effect and safety remain uncertain. This study aimed to summarize the evidence for vadadustat in the treatment of CKD patients with anemia. Methods: PubMed, Ovid Medline, Embase, Cochrane CENTRAL, Wanfang Data, China National Knowledge Infrastructure and an international trial register were searched from their inception to June 2021 for randomized controlled trials (RCTs) comparing the efficacy and safety of vadadustat to those of placebo or erythropoiesis-stimulating agents (ESAs) in treating anemia in CKD patients. Data were pooled in a meta-analysis, with results expressed as the mean difference for continuous outcomes and relative risk for categorical outcomes with 95% conﬁdence intervals (95% CIs). The certainty of evidence was rated according to Cochrane methods and the GRADE approach. Results: Ten RCTs comparing vadadustat with placebo (4 RCTs) or darbepoetin alfa (6 RCTs) were included (n=8489 participants). Compared with placebo, vadadustat increased the hemoglobin (Hb) response rate (risk ratio 5.27; 95% CI: 2.69 to 10.31; P<0.001; high certainty of evidence) and Hb level from baseline (∆Hb) (mean difference (MD) 1.35; 95% CI: 0.92 to 1.77; P<0.001; low certainty of evidence). Compared with placebo or darbepoetin alfa, vadadustat decreased hepcidin (MD -36.62; 95% CI: -54.95 to -18.30; P<0.001) and ferritin (MD -56.24; 95% CI: -77.37 to -35.11; P<0.001) levels and increased iron-binding capacity (MD 24.38; 95% CI: 13.69 to 35.07; P<0.001), with a low to moderate certainty of evidence. Moderate to high certainty evidence suggested that compared with placebo or darbepoetin alfa, vadadustat significantly increased the risk of nausea and diarrhea but did not significantly increase the risk of serious adverse events, especially all-cause mortality, cardiac events and nonfatal stroke. Conclusions: Vadadustat may safely improve Hb levels and promote iron utilization in CKD patients with anemia without increasing the incidence of serious adverse events.